Flowity – Artificial Intelligence for traffic analysis - Tedblad, Roger; Paoli, Marco (Proceedings from the Annual Transport Conference at Aalborg University, 2019)
Flowity is a product developed by ÅF. It brings cutting edge artificial intelligence technology to a wide range of markets. By utilizing Deep Neural Nets (DNN), Flowity is able to detect and track objects such as pedestrians and vehicles in streaming video. The product is highly versatile and can run on any type of camera or CCTV setup, with the ability to output the AI sensor data in real time. Flowity can be run as a real time system, where the sensor data is immediately available to act on by customized integrations; or as a sole analysis tool, where data is collected over time and made available for automatic report generation. This can form the basis for advanced business intelligence or be used as a foundation for other types of decision making.